PENGARUH INDEPENDENSI, OBYEKTIFITAS, PENGALAMAN KERJA, PENGETAHUAN, SERTA INTEGRITAS AUDITOR TERHADAP KUALITAS HASIL AUDIT DI LINGKUNGAN PEMERINTAH DAERAH PROVINSI SULAWESI UTARA - Ilat, Ventje; Saerang, David P.E.; Wokas, Heince R.N. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
The objectives of this research to empirically analyze the influence of independency, objectivity, job experience, knowledge, integrity, of audit quality. The population in this research are all auditor’s who worked on the Inspectorate of the city/ county in north Sulawesi. Sampling was conducted using a purposive sampling method and number of samples of 112 respondents. Primary data collection method used is questionnaire method. The data analysis technique used in This research is the technique of multiple regression analysis. The result showed that the independence, knowledge and integrity of the variables do not have a significant impact on audit quality. While the objectivity and job experience have a significant impact on audit quality